1987
DOI: 10.1128/aac.31.11.1697
|View full text |Cite
|
Sign up to set email alerts
|

Determination of in vitro susceptibility of Mycobacterium avium complex isolates to antimycobacterial agents by various methods

Abstract: Various methods were used to determine the in vitro susceptibility of Mycobacterium avium complex strains isolated from patients with acquired immunodeficiency syndrome. Our results confirm the noted resistance of the M. avium complex to conventional antituberculosis agents. The procedures used were both agar dilution and broth dilution, including a commercially available radiometric system (BACTEC; Johnston Laboratories, Towson, Md.). In general, all strains were more resistant by an agar dilution procedure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 22 publications
1
64
1
Order By: Relevance
“…In a previous study this compound was identified as having excellent MICs for a large panel of M. avium isolates (21), and the findings of the present study now confirm that the activity of this compound is indeed bactericidal within the infected host cell.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In a previous study this compound was identified as having excellent MICs for a large panel of M. avium isolates (21), and the findings of the present study now confirm that the activity of this compound is indeed bactericidal within the infected host cell.…”
Section: Discussionsupporting
confidence: 71%
“…Existing treatment regimens are primarily based on early results in the field in which multiple clinical isolates were tested for their in vitro susceptibilities to a wide variety of drugs, with the two most widely used methods being the broth microdilution method (43) and the radiometric BACTEC method (15,21). In both of these methods, the antimicrobial agent is added directly to broth cultures, and hence is in direct contact with the bacilli.…”
mentioning
confidence: 99%
“…This has led to studies comparing different methods of susceptibility testing (244) and demonstration that the growth stage of mycobacteria influences antibiotic susceptibility (558). However, methods of susceptibility testing may not be entirely at fault.…”
Section: Chemotherapy Of Nontuberculous Mycobacterial Infectionsmentioning
confidence: 99%
“…To confirm the initial observation in vivo, the bactericidal activity of EDP-420 was determined, as previously reported (17,24), and the concentration was used in vitro to determine the frequency of natural resistance to EDP-420 in a population of MAC. Inocula of 10 7 to 10 11 bacteria were incubated with 32 g/ml of EDP-420 in 7H9 broth for one week to select for resistant bacteria, and then bacteria were plated onto 7H10 agar with or without 32 g/ml of EDP-420 to isolate resistant mutants.…”
Section: Methodsmentioning
confidence: 99%
“…MICs were determined by a radiometric broth nanodilution method and the T100 method of data analysis (17). The inoculum for the susceptibility testing was prepared by obtaining 5 to 10 colonies from a 7H11 agar plate and placing them into 7H9 broth; the samples were then tested directly or frozen at Ϫ70°C.…”
Section: Methodsmentioning
confidence: 99%